Blood pressure control and mortality in US‐ and foreign‐born blacks in New York City. Issue 10 (6th July 2017) - Gyamfi, Joyce; Butler, Mark; Williams, Stephen K.; Agyemang, Charles; Gyamfi, Lloyd; Seixas, Azizi; Zinsou, Grace Melinda; Bangalore, Sripal; Shah, Nirav R.; Ogedegbe, Gbenga
Abstract : This retrospective cohort study compared blood pressure (BP) control (BP <140/90 mm Hg) and all‐cause mortality between US‐ and foreign‐born blacks. We used data from a clinical data warehouse of 41 868 patients with hypertension who received care in a New York City public healthcare system between 2004 and 2009, defining BP control as the last recorded BP measurement and mean BP control. Poisson regression demonstrated that Caribbean‐born blacks had lower BP control for the last BP measurement compared with US‐ and West African–born blacks, respectively (49% vs 54% and 57%; P <.001). This pattern was similar for mean BP control. Caribbean‐ and West African–born blacks showed reduced hazard ratios of mortality (0.46 [95% CI, 0.42–0.50] and 0.28 [95% CI, 0.18–0.41], respectively) compared with US‐born blacks, even after adjustment for BP. BP control rates and mortality were heterogeneous in this sample. Caribbean‐born blacks showed worse control than US‐born blacks. However, US‐born blacks experienced increased hazard of mortality. This suggests the need to account for the variations within blacks in hypertension management.